Diabetes Melitus Tipe 2 dengan Hipertiroid dan Hipertensi: Case Report - Akelba, Shalsa Damai; Putu Wika Pramesti Iswari; Adam Trojan Alisyahbana; Aulia Dwi Hendriani; Baiq Ramdhani Amelia Negara; Grandis Cristagalli1, Izza Mufida; M. Andre Darmawan; Nadia Safira; Ni Putu Visty Wedhiani; Rike Delya Rizqina; Tri Sastra Pradhini; Indah Sapta Wardani (Faculty of Medicine, Universitas Mataram, 2023)
Diabetes mellitus (DM) is high levels of glucose in the blood (hyperglycemia) accompanied by disturbances in carbohydrate, lipid, protein metabolism as a result of insufficiency of insulin function which can be caused by impaired or deficient insulin production by beta cells in the pancreas or can also be caused by a lack of responsiveness of insulin cells. The prevalence of diabetes mellitus is 9.3% or around 463 million people suffer from diabetes in 2019. One of the risk factors for diabetes mellitus is hyperthyroidism and hypertension. The right treatment for patients suffering from type 2 diabetes mellitus with hyperthyroidism and hypertension is to reduce glucose levels, blood pressure, and reduce the production of the thyroid gland